Light conversion material and preparation method and application thereof
By using a specific composition of the light conversion material with a chemical formula of LiaSrbMcGddREeNbfAgOh:mMn4+, it is prepared at high temperature. This solves the problem of poor stability of existing light conversion materials under humid and heat environment and ultraviolet light irradiation, and achieves the effect of efficient conversion of ultraviolet and green light to red light.
Patent Information
- Application Number
- CN202411926786.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-25
AI Technical Summary
Existing light conversion materials have poor stability under humid and heat environments and ultraviolet light irradiation, and have insufficient luminous intensity, so they cannot effectively convert ultraviolet and green light into red light that is beneficial to plant growth.
A photoconversion material with a specific composition is used, and the chemical formula is LiaSrbMcGddREeNbfAgOh:mMn4+, where M is Ca or Ba, RE is La or Y, and A is Ta, V or P. It is prepared by calcining at 1200-1500°C, and the use of cosolvents is avoided to improve the moisture-heat stability and luminous intensity of the material.
It is realized that ultraviolet light in the 300-380nm band and green light in the 480-550nm band are converted into red light in the 650-750nm band, which has excellent moisture and heat stability and ultraviolet aging resistance, and has high luminous intensity.
Smart Images

Figure CN119709200A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a light conversion material and a preparation method and application thereof. Background Art
[0002] The growth of plants requires the participation of sunlight, and light of different wavelengths has a great impact on the growth of plants. Blue-violet light (wavelength range of 400-480nm) can be absorbed by chlorophyll and carotenoids, promoting the growth of plant stems and leaves. Red-orange light (wavelength range of 600-700nm) can be absorbed by chlorophyll and promote the growth of plant fruits. Yellow-green light (wavelength range of 500-600nm) has almost no contribution to plant photosynthesis. Near-ultraviolet light (wavelength range of 315-400nm) will make plants shorter and leaves thicker, except for light with a wavelength of 360nm, which is beneficial to promoting the coloring of plant fruits. Ultraviolet light (wavelength range of 290-315nm) is harmful to most plants and will cause the aging and decay of agricultural films. Therefore, how to convert green light and ultraviolet light in sunlight that are not beneficial or harmful to plant growth into blue-violet light and red-orange light that are beneficial to photosynthesis has become the key.
[0003] CN118516115A discloses a red light conversion agent, the chemical formula of which is Ln2MN (1-x) O6:xMn 4+ ; Wherein, 0.1%≤x≤1.0%, Ln is at least one of La and Gd, M is at least one of Li and Mg; N is at least one of Nb, Sb and Al. The wet heat stability and UV aging resistance of the red light conversion agent are poor, and the strongest emission peak wavelength of the red light conversion agent is 715nm, which is closer to the infrared spectrum and has a low matching degree with the absorption band of chlorophyll a.
[0004] CN105001860A discloses a red phosphor, the chemical composition of which is as follows: a M b R c D d E e B f Al4O x :Mn 4 + y, wherein A is at least one of the monovalent elements Li, Na, K, Rb, and CS; M is at least one of the divalent elements Ca, Sr, Ba, Mg, Zn, Cd, Ni, and Pb; R is at least one of the trivalent elements Y, La, Ce, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and Bi; D is at least one of Sc, Ca, In, P, V, Nb, Ta, Si, Ge, Sn, Sb, Zr, Hf, Ti, and Cr; E is at least one of F, Cl, Br, and N; B is boron; Al is aluminum; O is oxygen; and Mn is Mg. 4+ It is tetravalent manganese. The red phosphor can convert near-ultraviolet light and blue light into red light.
[0005] CN118667540A discloses a near-infrared phosphor, comprising (A a D d M m R r Q q )E e G g An inorganic compound having Ca3Ga2Ge3O 12 The same cubic garnet structure; wherein the A element includes one or two of Ca, Sr, Ba, Bi, La and Ga; the D element includes one or two of Al, Ga, In and Sc; the M element includes one or two of Li, Mg and Zn; the R element includes one or two of Zr, Hf, Sn, Ti, Ta and Nb; the E element is selected from one or two of Si and Ge; the G element is selected from one or two of O, N and F; the Q element is selected from one or two of Mn, Eu, Cr and Ni. The phosphor can absorb light in the bands of 400-550nm and 600-800nm, and emit near-infrared light in the band of 1470-1602nm. Summary of the invention
[0006] In view of this, an object of the present invention is to provide a photoconversion material, which can convert ultraviolet light and green light into red light. Further, the photoconversion material has excellent wet heat stability and ultraviolet aging resistance. Further, the photoconversion material has a high luminous intensity. Another object of the present invention is to provide a method for preparing a photoconversion material. Another object of the present invention is to provide a use of the above-mentioned photoconversion material.
[0007] The present invention achieves the above-mentioned purpose through the following technical solutions.
[0008] In one aspect, the present invention provides a photoconversion material having a composition as shown in formula (1):
[0009] Li aSr b M c G d RE e Nb f A g O h :mMn 4+ (1);
[0010] Wherein, M is selected from one or more of Ca and Ba, RE is selected from one or more of La and Y, A is selected from one or more of Ta, V and P; 0.001≤a≤0.009, 0.3≤b≤2.2, 0≤c≤1.8, 0.3≤d≤0.8, 0.1≤e≤0.6, 0.3≤f≤1.2, 0≤g≤0.6, 4≤h≤8, 0.001≤m≤0.007;
[0011] Wherein, a, b, c, d, e, f, g, h and m represent the molar fraction or atomic fraction of each element respectively.
[0012] According to the light conversion material of the present invention, preferably, 0.5≤c≤1.5, and b+c=2.
[0013] According to the light conversion material of the present invention, preferably, 0.1≤g≤0.5, f+g=0.996, and d+e=1.
[0014] According to the light conversion material of the present invention, preferably, 0.003≤a≤0.007, 0.4≤d≤0.7, 0.2≤e≤0.5, 5≤h≤7, and 0.003≤m≤0.006.
[0015] According to the photoconversion material of the present invention, preferably, the M is Ca, the RE is La, and the A is P.
[0016] According to the photoconversion material of the present invention, preferably, the photoconversion material has one of the following chemical compositions:
[0017] Li 0.004 SxG 0.6 La 0.4 Nb 0.996 O6:0.004Mn 4+ ;
[0018] Li 0.004 Sr 0.8 Ca 1.2 G 0.6 La 0.4 Nb 0.996 O6:0.004Mn 4+ ;
[0019] Li 0.004 Sr0.8 Ca 1.2 G 0.6 La 0.4 Nb 0.5976 P 0.3984 O6:0.004Mn 4+ .
[0020] According to the photoconversion material of the present invention, preferably, the photoconversion material has a Sr2GdNbO6 crystal structure.
[0021] In another aspect, the present invention provides a method for preparing the above-mentioned light conversion material, comprising the following steps:
[0022] The raw materials obtained according to the composition of the light conversion material are calcined at 1200 to 1500° C. to obtain the light conversion material.
[0023] According to the preparation method of the present invention, preferably, no co-solvent is used during the preparation process.
[0024] In another aspect, the present invention provides use of the above-mentioned light conversion material in converting ultraviolet light in the 300-380 nm band and / or green light in the 480-550 nm band into red light in the 650-750 nm band.
[0025] The light conversion material of the present invention can convert ultraviolet light and green light into red light, and has excellent moisture and heat stability and ultraviolet aging resistance. Further, the light conversion material of the present invention has a high luminous intensity. The present invention has found that not using a co-solvent such as boric acid during the preparation process helps to improve the luminous intensity of the light conversion material, as well as the moisture and heat stability and ultraviolet aging resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 2 are XRD diagrams of the light conversion materials of Example 4 and Comparative Example 1.
[0027] Figure 2 The emission spectra of the light conversion materials of the embodiments and comparative examples under the excitation of ultraviolet light of the strongest excitation wavelength corresponding thereto.
[0028] Figure 3 The excitation spectra of the light conversion materials of the embodiments and comparative examples under monitoring at their corresponding emission main peak wavelengths are shown.
[0029] Figure 4 This is a graph showing the trend of the main peak intensity of the light conversion material of Example 4 as a function of the number of days of wet heat treatment.
[0030] Figure 5 This is a graph showing the variation trend of the main peak intensity of the light conversion material of Example 4 with the number of days of QUV aging treatment. DETAILED DESCRIPTION
[0031] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0032] <Light conversion materials>
[0033] The photoconversion material of the present invention has a composition shown in formula (1):
[0034] Li a Sr b M c G d RE e Nb f A g O h :mMn 4+ (1).
[0035] Li represents lithium element. a represents the molar fraction or atomic fraction of Li. 0.001≤a≤0.009; preferably, 0.003≤a≤0.007; more preferably, 0.004≤a≤0.005.
[0036] Sr represents strontium. b represents the molar fraction or atomic fraction of Sr. 0.3≤b≤2.2. In some embodiments, 1.8≤b≤2. In other embodiments, 0.8≤b≤1.
[0037] M is selected from one or more of Ca and Ba. Preferably, M is Ca. c represents the molar fraction or atomic fraction of M. 0≤c≤1.8; preferably, 0.5≤c≤1.5; more preferably, 1≤c≤1.2. In some embodiments, b+c=2.
[0038] Gd represents the rare earth element gadolinium. d represents the molar fraction or atomic fraction of Gd. 0.3≤d≤0.8; preferably, 0.4≤d≤0.7; more preferably, 0.5≤d≤0.6.
[0039] RE is selected from one or more of La and Y. Preferably, RE is La. 0.1≤e≤0.6; preferably, 0.2≤e≤0.5; more preferably, 0.3≤e≤0.4. In certain embodiments, d+e=1.
[0040] Nb represents the transition metal element niobium. f represents the molar fraction or atomic fraction of Nb. 0.3≤f≤1.2. In some embodiments, 0.8≤f≤1.0; preferably, 0.9≤f≤0.996. In other embodiments, 0.5≤f≤0.65; preferably, 0.55≤f≤0.5976.
[0041] A is selected from one or more of Ta, V, and P. Preferably, A is P. g represents the molar fraction or atomic fraction of A. 0≤g≤0.6; preferably, 0.1≤g≤0.5; more preferably, 0.3≤g≤0.3984. In some embodiments, f+g=0.996.
[0042] O represents an oxygen element. h represents a molar fraction or an atomic fraction of O. 4≤h≤8; preferably, 5≤h≤7; more preferably, 6≤h≤6.5.
[0043] Mn represents manganese. m represents the molar fraction or atomic fraction of Mn. 0.001≤m≤0.007; preferably, 0.003≤m≤0.006; more preferably, 0.004≤m≤0.005. In certain embodiments, f+g+m=1.
[0044] According to one embodiment of the present invention, the photoconversion material has a composition as shown below:
[0045] Li 0.004 SxG 0.6 La 0.4 Nb 0.996 O6:0.004Mn 4+ ;
[0046] Li 0.004 Sr 0.8 Ca 1.2 G 0.6 La 0.4 Nb 0.996 O6:0.004Mn 4+ ;
[0047] Li 0.004 Sr 0.8 Ca 1.2 G 0.6 La 0.4 Nb 0.5976 P 0.3984 O6:0.004Mn 4+ .
[0048] The above-mentioned element composition and content are helpful to improve the luminous intensity, wet heat stability and UV aging resistance of the light conversion material.
[0049] The light conversion material of the present invention has a Sr2GdNbO6 crystal structure.
[0050] The strongest emission peak of the photoconversion material of the present invention under the excitation of the strongest excitation wavelength ultraviolet light corresponding to it is 650-690nm. In some embodiments, it is 670-685nm. The photoconversion material of the present invention has a high matching degree with the absorption band of chlorophyll a.
[0051] <Method for preparing light conversion material>
[0052] The preparation method of the photoconversion material of the present invention comprises the following steps: calcining the raw material obtained according to the composition of the photoconversion material at 1200-1500° C. to obtain the photoconversion material. In some embodiments, the raw material and the cosolvent are calcined at 1200-1500° C. to obtain the photoconversion material. Examples of the cosolvent include but are not limited to H3BO3. The amount of the flux can be 1-10% of the mass of the raw material; preferably 3-6%.
[0053] The raw materials may be mixed and then ground or ball-milled before calcination. A co-solvent may be added during the grinding or ball-milling process.
[0054] The calcination temperature is 1200-1500°C, preferably 1300-1400°C. The calcination time can be 6-15 hours, preferably 7-10 hours. The calcination can be carried out in an air atmosphere. The calcination can be carried out in a muffle furnace.
[0055] The Li source may be Li2CO3. The Sr source may be SrCO3. The Gd source may be Gd2O3. The La source may be La2O3. The Nb source may be Nb2O5. The Mn source may be MnO2. The Ca source may be CaCO3. The P source may be (NH4)2HPO4. Preferably, no flux is used in the preparation process.
[0056] <Application of Photoconversion Materials>
[0057] The light conversion material of the present invention can convert ultraviolet light in the wavelength band of 300-380nm and green light in the wavelength band of 480-550nm into red light in the wavelength band of 650-750nm. Therefore, the present invention provides the use of the above light conversion material in converting ultraviolet light in the wavelength band of 300-380nm and / or green light in the wavelength band of 480-550nm into red light in the wavelength band of 650-750nm.
[0058] The light conversion material of the present invention can convert ultraviolet light and green light into red light which is beneficial to plants, and the light conversion material of the present invention can be applied to agricultural films.
[0059] Examples 1 to 4 and Comparative Example 1
[0060] Li2CO3 was used as a Li source, SrCO3 was used as a Sr source, Gd2O3 was used as a Gd source, La2O3 was used as a La source, Nb2O5 was used as a Nb source, MnO2 was used as a Mn source, CaCO3 was used as a Ca source, and (NH4)2HPO4 was used as a P source. Raw materials were prepared according to the chemical composition of the photoconversion material shown in Table 1.
[0061] The raw material was placed in an agate mortar and ground for 30 minutes; if H3BO3 co-solvent was used, H3BO3 was added to the agate mortar and further ground together with the raw material to obtain a ground raw material.
[0062] The ground raw materials were calcined in a muffle furnace in an air atmosphere at 1400° C. for 8 h, and naturally cooled to 25° C. to obtain a light conversion material.
[0063] The chemical composition of the photoconversion material and the amount of H3BO3 used are shown in Table 1.
[0064] Table 1
[0065] Serial number Chemical composition of light conversion materials <![CDATA[Dosage of H3BO3]]> Example 1 <![CDATA[Li 0.004 Sr2Gd 0.6 The 0.4 Nb 0.996 O6:0.004Mn 4+ ]]> 4% of raw material mass Example 2 <![CDATA[Li 0.004 Sr2Gd 0.6 The 0.4 Nb 0.996 O6:0.004Mn 4+ ]]> — Example 3 <![CDATA[Li 0.004 Sr. 0.8 That 1.2 Gd 0.6 to 0.4 Nb 0.996 O6:0.004Mn 4+ ]]> — Example 4 <![CDATA[Li 0.004 Sr. 0.8 That 1.2 Gd 0.6 to 0.4 Nb 0.5976 P 0.3984 O6:0.004Mn 4+ ]]> — Comparative Example 1 <![CDATA[Li 0.004 Sr2GdNb 0.996 O6:0.004Mn 4+ ]]> 4% of raw material mass
[0066] Note: “—” means H3BO3 is not used.
[0067] Experimental example
[0068] XRD: Figure 1 4 and 1 are XRD patterns of the light conversion materials of Example 4 and Comparative Example 1. Figure 1 It can be seen that the light conversion material of the present invention has a double perovskite crystal structure of Sr2GdNbO6.
[0069] Emission spectrum: Figure 2 The emission spectra of the photoconversion materials of the embodiments and comparative examples under the excitation of the corresponding strongest excitation wavelength ultraviolet light. Among them, the strongest excitation wavelength ultraviolet light of the photoconversion material of embodiment 1 is 347nm, the strongest excitation wavelength ultraviolet light of the photoconversion material of embodiment 2 is 344nm, the strongest excitation wavelength ultraviolet light of the photoconversion material of embodiment 3 is 312nm, the strongest excitation wavelength ultraviolet light of the photoconversion material of embodiment 4 is 310nm, and the strongest excitation wavelength ultraviolet light of the photoconversion material of comparative example 1 is 345nm. Figure 2 It can be seen that the emission spectra of Examples 1 to 4 gradually shift from two peaks (667nm, 684nm) to one peak (684nm), and the luminescence intensity gradually increases. The luminescence intensity of the light conversion material of Example 4 is 22 times that of Comparative Example 1.
[0070] Excitation spectrum: Figure 3 The excitation spectra of the photoconversion materials of the embodiments and comparative examples under the monitoring of their corresponding emission main peak wavelengths are shown in Figures 1 and 2. The emission main peak wavelength of the photoconversion material of Embodiment 1 is 667nm, the emission main peak wavelength of the photoconversion material of Embodiment 2 is 685nm, the emission main peak wavelength of the photoconversion material of Embodiment 3 is 684nm, the emission main peak wavelength of the photoconversion material of Embodiment 4 is 684nm, and the emission main peak wavelength of the photoconversion material of Comparative Example 1 is 667nm. Figure 3It can be seen that the excitation regions of the light conversion material of the present invention are the violet region and the green region. From Example 1 to Example 4, the excitation peak of the green region red-shifts and gradually approaches 510nm; the excitation peak of the violet region gradually shifts from two peaks (315nm, 345nm) to one peak (310nm).
[0071] Wet heat stability: The photoconversion material was subjected to wet heat treatment at a temperature of 85°C and a humidity of 80%. The emission spectra of the photoconversion material of Example 4 before and after wet heat treatment were tested under the condition of using ultraviolet light with the strongest excitation wavelength of 310 nm as the excitation light. The ratio (I) of the emission main peak intensity of the photoconversion material after wet heat treatment for different times to the emission main peak intensity of the photoconversion material before wet heat treatment was calculated as follows: Figure 4 As shown. Figure 4 It can be seen that after 6 days of wet heat treatment, the I value of the photoconversion material of Example 4 can still be maintained at 93.25%, which has good wet heat stability.
[0072] Anti-ultraviolet aging performance: The photoconversion material was irradiated with 340nm ultraviolet light for ultraviolet aging treatment. The emission spectrum of the photoconversion material of Example 4 before and after aging treatment was tested under the condition of using the strongest excitation wavelength 310nm ultraviolet light as the excitation light. The ratio (P) of the emission main peak intensity of the photoconversion material after aging treatment for different time periods to the emission main peak intensity of the photoconversion material before aging treatment was calculated as follows: Figure 5 As shown. Figure 5 It can be seen that after 9 days of QUV aging treatment, the P value of the light conversion material in Example 4 can still be maintained at 95.89%, and has good UV aging resistance.
[0073] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.
Claims
1. A light conversion material, characterized in that: The photoconversion material has a composition shown in formula (1): Li a Sr b M c God d RE e No f A g O h :mMn 4+ (1); Wherein, M is selected from one or more of Ca and Ba, RE is selected from one or more of La and Y, A is selected from one or more of Ta, V and P; 0.001≤a≤0.009, 0.3≤b≤2.2, 0≤c≤1.8, 0.3≤d≤0.8, 0.1≤e≤0.6, 0.3≤f≤1.2, 0≤g≤0.6, 4≤h≤8, 0.001≤m≤0.007; Wherein, a, b, c, d, e, f, g, h and m represent the molar fraction or atomic fraction of each element respectively.
2. The light conversion material according to claim 1, characterized in that 0.5≤c≤1.5, b+c=2.
3. The light conversion material according to claim 1, characterized in that 0.1≤g≤0.5, f+g=0.996, d+e=1.
4. The light conversion material according to claim 1, characterized in that 0.003≤a≤0.007, 0.4≤d≤0.7, 0.2≤e≤0.5, 5≤h≤7, 0.003≤m≤0.
006.
5. The light conversion material according to claim 1, characterized in that: The M is Ca, the RE is La, and the A is P.
6. The light conversion material according to claim 1, characterized in that: The photoconversion material has a chemical composition as shown below: The 0.004 Sr2Gd 0.6 The 0.4 Nb 0.996 O6:0.004Mn 4+ ; them 0.004 Sr. 0.8 That 1.2 Gd 0.6 to 0.4 Nb 0.996 O6:0.004Mn 4+ ; them 0.004 Sr. 0.8 That 1.2 Gd 0.6 to 0.4 Nb 0.5976 P 0.3984 O6:0.004Mn 4+ 。 7. The light conversion material according to any one of claims 1 to 6, characterized in that: The light conversion material has a Sr2GdNbO6 crystal structure.
8. The method for preparing a light conversion material according to any one of claims 1 to 7, characterized in that: The steps include: The raw materials obtained according to the composition of the light conversion material are calcined at 1200 to 1500° C. to obtain the light conversion material.
9. The preparation method according to claim 8, characterized in that: No co-solvent was used during the preparation process.
10. Use of the light conversion material according to any one of claims 1 to 7 for converting ultraviolet light in the wavelength band of 300 to 380 nm and / or green light in the wavelength band of 480 to 550 nm into red light in the wavelength band of 650 to 750 nm.
Citation Information
Patent Citations
Dark red light niobate fluorescent powder for agricultural lighting and preparation method thereof
CN112625684A